Innovating the treatment of COPD exacerbations: a phone interactive telesystem to increase COPD Action Plan adherence - Jean Bourbeau; Raquel Farias; Maria Sedeno; Danielle Beaucage; Isabelle Drouin; Isabelle Ouellet; Alexandre Joubert; Rita Abimaroun; Meena Patel; Mira Abou Rjeili (BMJ Open Respiratory Research, 2019)
Introduction Self-management interventions with Written Action Plans and case management support have been shown to improve outcomes in patients with chronic obstructive pulmonary disease (COPD). Novel telehealth technologies may improve self-management interventions. The objectives of this study were to determine whether the use of an interactive phone telesystem increases Action Plan adherence, improves exacerbation recovery and reduces healthcare use in a real-life practice of a COPD clinic.Methods Initially, 40 patients were followed by a COPD telesystem for 1 year. Detailed data from patients’ behaviours during exacerbations was recorded. The telesystem use was then extended to 256 patients from a real-life COPD clinic. Healthcare utilisation for the year before and after telesystem enrolment was then assessed through hospital administrative databases.Results Thirty-three of the 40 patients completed the initial 1-year study. Eighty-one exacerbations were reported in the 1-year follow-up. Action Plan adherence was observed for 72% of the exacerbations and those who were adherent had a significantly faster exacerbation recovery time. The large-scale implementation of the telesystem resulted in a significant decrease in the proportion of patients with ≥1 respiratory-related emergency room (ER) visits (120 before vs 110 after enrolment, p<0.001) and with ≥1 COPD-related hospitalisations (75 before vs 65 after enrolment, p<0.001).Discussion COPD Written Action Plan adherence was further enhanced with the use of telehealth technologies in a specialised clinic with experience in COPD self-management. Patients followed by the telesystem recovered faster from exacerbations and had a further decrease in COPD-related ER visits and hospitalisations.Trial registration number NCT02275078.